Effecting social change in the `smart city': the West End connect community project. - Lynn McAllister etal (Centre for Social Change Research, 2005)
Brisbane has declared itself a `smart city'. But more and more Brisbane is also becoming a digitally divided city. The Brisbane community is being separated into those who have access to and are comfortable using Information and Communication Technology (ICT) - the `haves' - and groups who do not have access to and are not comfortable using ICT - the `have-nots'. The social and economic implications of digitally divided communities cannot be ignored by government or society as whole. The inner city suburb of West End is an example of a socially, culturally and economically diverse community. The suburb has traditionally been home to Indigenous and migrant populations as well as being a refuge for many of Brisbane's homeless people. The demographics of this suburb, however, are being significantly altered by new property developments with wealthier residents choosing to move close to the city. West End is rapidly becoming a digitally divided community. This paper explores a case study in which the Queensland University of Technology and the State Library of Queensland worked in collaboration with a number of community groups in West End to help bridge the growing digital divide. The West End Connect Community Project began in November 2004 with the aim of providing the opportunity for West End community groups to develop the skills and knowledge vital for personal and vocational success in an ever-changing environment of digital information. The paper will discuss and evaluate the strategies used to deliver and develop a community education program that will lead to social change for West End. The paper will discuss the impact of the project on the West End community as a way of bridging the digital divide